Perubahan Sosial Terhadap Perkembangan Desa Rasau Jaya 3 Setelah Pembangunan Taman Bunga Rajati Flower Garden - Istiqomah, Istiqomah; Novitasari, Ragil Tri (Tanjungpura University, 2020)
The purpose of this study is for learning. This study entitled Social Change Towards Development of Rasau Jaya Village 3 After the Development of the Rajati Flower Garden. With the problem of how social change in the village of Rasau Jaya 3, economic improvement after the construction of a flower garden, development planning or the addition of facilities. This research method is a descriptive qualitative approach. Data sources of this research are primary data and secondary data. The results showed that: after the construction of the flower garden in Rasau Jaya 3 village the development of social change there was increasing, the people there accepted the development of the flower garden, because with the development of the community's economy there could be increased, because the people there could sell at around the flower garden so that it can increase their economy again there, and there will be plans to add facilities in the flower garden so that it can attract visitors to keep coming to the flower garden of the flower garden rajati.